Trajectories of illness perceptions in patients with kidney disease receiving dialysis: Relationship with psychological and physical symptoms - Buse Keskindag; Ken Farrington; Duriye Deren Oygar; Sam Norton; Shivani Sharma (PLoS ONE, 2025)
Illness perceptions play an important role in outcomes for patients with advanced kidney failure receiving dialysis, though they are rarely examined over a sustained period and in distinct cultural settings. This observational cohort study used a prospective longitudinal design to examine how illness perceptions change overtime. It also considered whether these trajectories are related to patient experience of psychological and physical symptoms including those associated with dialysis, and depressive mood. Data were collected from 181 patients recruited from four dialysis centres in Northern Cyprus between 2020–2021. There were 124 patients receiving dialysis (91.1% haemodialysis) and 57 patients in the pre-dialysis phase at baseline. Self-reported measures including the Brief Illness Perception Questionnaire, Patient Health Questionnaire-9, and Dialysis Symptom Index, were completed at the start (time 1) of the study and then again at six months (Time 2) and at 12 months (Time 3) using versions validated in the local language (Turkish). Multilevel Models (MLM) for repeated measures were used to understand trajectories of illness perceptions over the 12-months of follow-up. On average, perceptions of consequences and emotional response to illness decreased over a one-year period. Depressive symptoms and dialysis symptom burden were found to be relatively stable over the same period. However, patients who reported higher perceptions of illness consequences and emotional response at baseline were more likely to report greater depressive symptoms at 12 months. Similarly, those already receiving dialysis who reported greater emotional response and lower levels of personal control at baseline were more likely to continue to report higher dialysis symptom burden at 12 months. The findings underscore the importance of illness perceptions as a framework to identify patients who may benefit from support, importantly offering an anchor for intervention design. Establishing cultural acceptability of such an approach will be an important next step.